Developmental aortic arch anomalies in infants and children assessed with CT angiography - Ramos-Duran, Luis; Henzler, Thomas; Apfaltrer, Paul (American journal of roentgenology, 2012)
OBJECTIVE: The purpose of this article is to review the normal anatomy of the aortic arch and the most common variations of congenital aortic arch anomalies using low-radiation-dose, defined as a dose-length product of 7–15 mGy x cm, MDCT angiography. CONCLUSION: Radiologists should be prepared to fully describe congenital aortic arch anomalies; recognize them on CT angiography, especially the presence or absence of vascular rings or aberrant arteries; and explain their association with the trachea and esophagus.